Involvement of Phosphatidylinositol 3-kinase in the regulation of proline catabolism in Arabidopsis thaliana - Leprince, Anne-Sophie; Magalhaes, Nelly; De Vos, Delphine; Bordenave, Marianne; Crilat, Emilie; Clément, Gilles; Meyer, Christian; Munnik, Teun; Savouré, Arnould (Frontiers in Plant Science, 2015)
Plant adaptation to abiotic stresses such as drought and salinity involves complex regulatory processes. Deciphering the signalling components that are involved in stress signal transduction and cellular responses is of importance to understand how plants cope with salt stress. Accumulation of osmolytes such as proline is considered to participate in the osmotic adjustment of plant cells to salinity. Proline accumulation results from a tight regulation between its biosynthesis and catabolism. Lipid signal components such as phospholipases C and D have previously been shown to be involved in the regulation of proline metabolism in Arabidopsis thaliana. In this study, we demonstrate that proline metabolism is also regulated by class-III Phosphatidylinositol 3-kinase (PI3K), VPS34, which catalyses the formation of phosphatidylinositol 3-phosphate (PI3P) from phosphatidylinositol. Using pharmacological and biochemical approaches, we show that the PI3K inhibitor, LY294002, affects PI3P levels in vivo and that it triggers a decrease in proline accumulation in response to salt treatment of A. thaliana seedlings. The lower proline accumulation is correlated with a lower transcript level of Pyrroline-5-carboxylate synthetase 1 biosynthetic enzyme and higher transcript and protein levels of Proline dehydrogenase 1 (ProDH1), a key-enzyme in proline catabolism. We also found that the ProDH1 expression is induced in a pi3k-hemizygous mutant, further demonstrating that PI3K is involved in the regulation of proline catabolism through transcriptional regulation of ProDH1. A broader metabolomic analysis indicates that LY294002 also reduced other metabolites, such as hydrophobic and aromatic amino acids and sugars like raffinose.